REKONSTRUKSI DAN REAKTUALISASI HUKUM ISLAM - Ratno, Dedi (Program Studi Hukum Tata Negara, 2021)
Munawir Sjadzali's main concern lies in the premise that there are a number of verses of the Qur'an, especially those relating to social issues, not rituals that are not in accordance with today's needs, such as inheritance law, slavery and bank interest. In this matter, Munawir refers, among other things, to the spirit of caliph Umar bin Khattab's experience. This brave and honest pattern of ijtihad Umar bin Khattab has inspired Munawir to argue that the Muslim community should be honest and brave in dealing with Islamic law. Believing in the dynamics and vitality of shari'ah, he encouraged Muslims to actualize Islamic law.